Medical Thoracoscopy vs Closed Pleural Biopsy in Pleural Effusions: A Randomized Controlled Study - Nithya Haridas; Suraj K.P.; Rajagopal T.P.; James P.T.; Ravindran Chetambath (Journal of Clinical and Diagnostic Research, 2014)
Background: Pleural effusion is a common diagnostic dilemma for the pulmonologist. A histological diagnosis would many a time steer the way to an accurate diagnosis of the aetiologies of pleural effusions. This study has compared two methods for obtaining histological specimens in cases of undiagnosed pleural effusions. Aim: To compare the efficacy of closed pleural biopsy with Abrahm’s needle and medical thoracoscopic biopsy in the diagnosis of undiagnosed exudative pleural effusions at a tertiary care setting. Study Design: Randomized controlled study. Study Period: November 2008–October 2010. Methodology: All patients who were admitted with pleural effusions underwent a clinical workup for pleural effusions. Light’s criterion was used to differentiate between exudative and transudative pleural effusions. Those patients with exudative pleural effusions, who did not have a specific diagnosis, were included in the study. Fifty eight patients were included in the study and they were randomized into 2 Groups of 29 patients each. One group was subjected to medical thoracoscopic pleural biopsy and the other to closed pleural biopsy with Abrahm’s needle. Demographic, clinical and biochemical characteristics, diagnostic yields and the complications among the two groups were compared. Result: Medical thoracoscopy has a diagnostic yield of 86.2% with complication rate of 10.3% compared to 62.1% and 17.2% respectively in closed pleural biopsy group. Conclusion: Medical thoracoscopic pleural biopsy had a better diagnostic yield with a lower complication rate as compared to closed pleural biopsy with Abrahm’s needle.